2004
DOI: 10.2109/jcersj.112.586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ordered Arrangement of Ce and Zr Ions on Oxygen Storage Capacity of Ceria-Zirconia Solid Solution

Abstract: ZAWRjAÅnÌÌ_f \ÉyÚ·ZECIyÑWRjECIÌK¥zñÌe¿ {c¾FEEÇYERºÀbE]zìpvE²XØ µE·äNMEcÓ«MEY³(The CeO 2 ZrO 2 solid solution is the most important oxygen storage/release material for use in automobile catalysts. In particular, the ceriazirconia solid solution with a pyrochlore structure exhibits the highest oxygen storage capacity (OSC). In this study, CeO 2 ZrO 2 solid solutions containing Y 2 O 3 were synthesized and their OSCs were measured to clarify the influence of an ordered arrangement of Ce and Zr ions on the OSC. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 11 publications
5
44
0
Order By: Relevance
“…Accordingly, a considerable research effort has been devoted to gain a deeper understanding of the structural changes induced on the oxides by the ageing cycles mentioned above. A number of techniques, including X-ray diffraction (XRD) [13,14,18,20,23,24,31], EXAFS [29,30,31], Raman spectroscopy [14,17,18,24], High Resolution Electron Microscopy (HREM) [21,22,25,26] and High Angle Annular Dark Field Scanning-Transmission Electron Microscopy (HAADF-STEM) [25] have been applied in these structural investigations. Among them, XRD, Raman spectroscopy, and more recently HREM and HAADF-STEM have been the most extensively applied ones.…”
Section: Structural Studies On Thermally Aged Ceria-zirconia Mixed Oxmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, a considerable research effort has been devoted to gain a deeper understanding of the structural changes induced on the oxides by the ageing cycles mentioned above. A number of techniques, including X-ray diffraction (XRD) [13,14,18,20,23,24,31], EXAFS [29,30,31], Raman spectroscopy [14,17,18,24], High Resolution Electron Microscopy (HREM) [21,22,25,26] and High Angle Annular Dark Field Scanning-Transmission Electron Microscopy (HAADF-STEM) [25] have been applied in these structural investigations. Among them, XRD, Raman spectroscopy, and more recently HREM and HAADF-STEM have been the most extensively applied ones.…”
Section: Structural Studies On Thermally Aged Ceria-zirconia Mixed Oxmentioning
confidence: 99%
“…Despite the difficulty inherently associated to the eventual occurrence of such a large variety of phases, there are some structural facts which may be considered as well established. As outlined by a number of authors [13,18,20,23,26] order ↔ disorder phenomena induced on the Ce-Zr cationic sublattice by the SR-MO and SR-SO ageing treatments would play an essential role in determining their redox response. In effect, it is generally acknowledged that associated to SR-type reduction treatments an oxygen deficient, cation-ordered, pyrochlore-type phase, is formed.…”
Section: Structural Studies On Thermally Aged Ceria-zirconia Mixed Oxmentioning
confidence: 99%
See 2 more Smart Citations
“…The facilitated effect of Ce 4+ precursor instead of Ce 3+ one on the preparation of homogeneous bi-component material is reported in [20]. Suda et al [43] established that wet milling process provided formation of solid solution with complex morphological content. Sellick et al [11] reported minor increase of catalytic activity in naphthalene oxidation with Zr addition when precipitation by urea instead of carbonate was used.…”
Section: Introductionmentioning
confidence: 99%